ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENCEMARAN SUMBER DAYA AIR DI WILAYAH SUNGAI: SYSTEMATIC LITERATURE REVIEW - Saputra, Ade Jaya; Lestari, Sri Dewi; Ginting, Jody Martin (Jurnal Teknik Sipil dan Arsitektur, 2025)
Rivers are an important part of the ecosystems in several countries worldwide. They serve as a vital source of water for drinking, irrigation, and various other purposes. River pollution can lead to serious consequences for both the environment and human health. It can result in the death of aquatic life and render the water unsafe for human consumption. The research analysis was conducted using a literature review based on the factors influencing water resource pollution in river regions. The method used involved identifying the causal factors for scientific examination. The data was then processed using the Publish or Perish and VOS Viewer software. The results of the analysis regarding the number of factors affecting water resource pollution in river regions include the disposal of organic and non-organic waste, liquid waste, and Mandi, Cuci, Kakus (MCK) activities in the river areas. Overall, this systematic literature review provides a comprehensive overview of the factors and types of waste influencing water resource pollution in river regions. The study summarizes existing knowledge and research in this field, offering valuable insights and recommendations for practitioners and researchers involved in water resource pollution studies, especially in river regions. The Systematic Literature Review method presents an important overview of the factors influencing water resources in river regions. By comprehensively reviewing the literature, this journal identifies key factors causing water resource pollution in river environments and the challenges that need to be addressed for their effective implementation.